GO+ DALAM MENUNJANG INT+ UNTUK PENGELOLAAN DATA CMB PADA PERGURUAN TINGGI - Muhamad Yusup; Untung Rahardja; Susan Oktaviani (CCIT Journal, 2014)
The development of information technology , especially in the era of globalization software much influence on human life and the world of education. And supported by increased public participation in information technology to education in particular. Higher Education is a leading university that has had the best level of recognition from the National Accreditation Board makes a lot of enthusiasts who signed up. College Marketing Division has Integram system that supports data management Prospective New Students and can only be accessed on campus. Therefore we need a system that can be used online. To support this necessary or membership management student called INT +. There are four problems in the system that is running INTEGRAM system . There are three objectives in this study. Researchers using the prototype as a research method . Data collection techniques used were observation to stakeholders in the marketing division . This study is limited to the process of getting the data presentation area in the form of name , email and telephone number Prospective New Student . GO + is the latest version of GO that are connected to the Internet can be accessed anywhere. In the implementation shown prototype GO+ with INT+ , so it can be concluded that GO + with INT+ to maximize the performance of Personil Marketing .